2020
DOI: 10.1101/2020.07.27.20163212
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association between Alzheimer’s disease and COVID-19: A bidirectional Mendelian randomization

Abstract: Background In observational studies, Alzheimer's disease (AD) has been associated with an increased risk of Coronavirus disease 2019 (COVID-19), and the prognosis of COVID-19 can affect nervous systems. However, the causality between these conditions remains to be determined. Methods This study sought to investigate the bidirectional causal relations of AD with COVID-19 using two-sample Mendelian randomization (MR) analysis. Results We found that genetically predicted AD was significantly associated with highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Future genetic analyses with larger sample sizes or clinical experiments are required to fully identify the relationship between smoking and COVID-19. The genetically predicted late-onset AD was also shown to be significantly associated with a higher risk of infection based on both UKBB and HGI report, which is not observed in another recent MR analysis 64 . This is possibly due to the larger case number (35,274 compared with 17,008) was included in late-onset AD GWAS, thus increased the power of the MR analysis.…”
Section: Discussionmentioning
confidence: 78%
“…Future genetic analyses with larger sample sizes or clinical experiments are required to fully identify the relationship between smoking and COVID-19. The genetically predicted late-onset AD was also shown to be significantly associated with a higher risk of infection based on both UKBB and HGI report, which is not observed in another recent MR analysis 64 . This is possibly due to the larger case number (35,274 compared with 17,008) was included in late-onset AD GWAS, thus increased the power of the MR analysis.…”
Section: Discussionmentioning
confidence: 78%
“…82 Another study that was published in a peer-reviewed journal showed accelerated ageing was associated with higher COVID-19 risk, although the publication was not indexed in PubMed. 102 However, there were methodological concerns in some studies, such as interpreting liability as the effect of disease diagnosis, 87 the lack of comprehensive assessment of IV assumptions 96 and insufficient details for replication. 100 …”
Section: Resultsmentioning
confidence: 99%
“…For instance, BMI and smoking are associated with an increased COVID-19 risk, while no evidence of causal effects was found for circulating 25-hydroxyvitamin D (25OHD) levels [18][19][20] . However, inconsistent results were also reported for some factors, such as Alzheimer's disease, blood lipids, and physical activity 18,19,[21][22][23][24][25][26] . Some of these inconsistencies are likely due to the usage of early genome-wide association studies (GWAS) of COVID-19, which have small sample sizes.…”
Section: Introductionmentioning
confidence: 99%